A Note on the Area under the Gains Chart - Lloyd, Chris J. (International Journal of Statistics in Medical Research, 2018)
The Receiver Operating Characteristic (ROC) chart is well known in medicine and machine learning. In particular the area under the ROC chart measures the probability of correct selection in a two alternative forced choice (2AFC) scenario. The gains chart is closely related to the ROC curve but carries extra information about the rate at which the classifier identifies response, information that is not carried by the ROC chart. In this note, we point out that the appropriate area under the gains chart is identical to the analogous area under the ROC chart and that the gains chart is therefor to be preferred as a summary of classifier success.